Prevalence of protective antibody against measles in HIV-infected children with immune recovery after highly active antiretroviral therapy - Aurpibul L. (2014)
Objectives: This study was conducted to determine the prevalence of measles-protective antibody in HIV-infected children with immune recovery after highly active antiretroviral therapy (HAART). Methods: Ninety-six HIV-infected children were enrolled in the study. Their mean age was 9.7±2.6 years, 47% were boys, and 47% were in Centers for Disease Control and Prevention (CDC) clinical category C. All participants had been treated with HAART until they achieved a CD4 cell percentage ≥15%. Three children with a history of clinical measles infection were not included in the data analysis. Results: Only 39 out of 93 children (42%) had a measles-protective antibody level, defined as an anti-measles immunoglobulin G (IgG) level ≥320mIU/mL. There was no significant difference between the groups with and without protective levels of measles antibody in gender, clinical category, age at which HAART was started, duration of severe immune suppression, CD4 cell count and percentage, or plasma HIV RNA level before and after HAART. Conclusions: We conclude that, despite a history of measles immunization and evidence of immune reconstitution after HAART, many healthy HIV-infected children are still susceptible to measles. © 2006 British HIV Association.